2022
DOI: 10.7189/jogh.12.05002
|View full text |Cite
|
Sign up to set email alerts
|

Reduced alcohol consumption during the COVID-19 pandemic: Analyses of 17 000 patients seeking primary health care in Colombia and Mexico

Abstract: Background During the COVID-19 pandemic, an increase of heavy alcohol use has been reported in several high-income countries. We examined changes in alcohol use during the pandemic among primary health care (PHC) patients in two middle income countries, Colombia and Mexico. Methods Data were collected during routine consultations in 34 PHC centres as part of a large-scale implementation study. Providers measured patients’ alcohol consumption with the three item ‘Alcohol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
5
0
3
Order By: Relevance
“…61 While anecdotal information indicated protective effects of smoking tobacco and cannabis (in contrast to cannabidiol 62 ), clinical data overwhelmingly documented that individuals with SUDs were more likely to require hospitalization or die due to COVID-19 (Wang et al, 2021), those with opioid use disorders being particularly at high risk. Despite expectations that pandemic-related stress would promote heavier substance use, results were mixed for substances such as alcohol 63,64 and indicative of escalating use for others, such as opioids and polysubstance use. 65,66 Collectively, these epidemiologic studies have shown robust phenotypic correlations between SUDs and these four medical conditions.…”
Section: Covid-19mentioning
confidence: 98%
“…61 While anecdotal information indicated protective effects of smoking tobacco and cannabis (in contrast to cannabidiol 62 ), clinical data overwhelmingly documented that individuals with SUDs were more likely to require hospitalization or die due to COVID-19 (Wang et al, 2021), those with opioid use disorders being particularly at high risk. Despite expectations that pandemic-related stress would promote heavier substance use, results were mixed for substances such as alcohol 63,64 and indicative of escalating use for others, such as opioids and polysubstance use. 65,66 Collectively, these epidemiologic studies have shown robust phenotypic correlations between SUDs and these four medical conditions.…”
Section: Covid-19mentioning
confidence: 98%
“…En otros países, durante la pandemia, se han identificado cambios en los patrones de consumo de alcohol; por un lado, mayor consumo entre consumidores de alto riesgo previos (es decir, quienes ya bebían en niveles excesivos antes de la pandemia de COVID-19) y, por otro lado, una disminución del consumo entre consumidores de alcohol de bajo riesgo (17). Esta tendencia también se observó en la Ciudad de México (15,18). Es preocupante que, entre quienes presentaron consumo de riesgo alto, 50,8% eran mujeres.…”
Section: Discussionunclassified
“…En la Ciudad de México, a partir de septiembre de 2019, se llevó a cabo una investigación cuasiexperimental denominada proyecto SCALA, con la finalidad de evaluar la mejor estrategia para la implementación de un modelo de detección, intervención breve y referencia para el tratamiento del consumo de alcohol en centros de salud de tres países latinoamericanos: Colombia, México y Perú (13)(14)(15). En el estudio se compraron los cambios en la medición del consumo de alcohol en cuatro condiciones experimentales en cada país.…”
Section: Análisisunclassified
“…Future studies could benefit from collecting data throughout a longer implementation of community support. In addition to impeded program implementation and health care delivery, the COVID-19 pandemic has also been linked to reduced alcohol consumption [ 27 ]. During this public health emergency, resources have been prioritised for more pressing health care issues than for preventive measures.…”
Section: Discussionmentioning
confidence: 99%